Draft genome sequence of the Brazilian toxic bloom-forming cyanobacterium Microcystis aeruginosa strain SPC777 - Fiore, Marli F.; Alvarenga, Danillo O.; Varani, Alessandro M. [UNESP]; Hoff-Risseti, Caroline; Crespim, Elaine; Ramos, Rommel T.J.; Silva, Artur; Schaker, Patricia D.C.; Heck, Karina; Rigonato, Janaina; Schneider, Maria Paula C. (American Society for Microbiology, 2013)
Microcystis aeruginosa strain SPC777 is an important toxin-producing cyanobacterium, isolated from a water bloom of the Billings reservoir (São Paulo State, Brazil). Here, we report the draft genome sequence and initial findings from a preliminary analysis of strain SPC777, including several gene clusters involved in nonribosomal and ribosomal synthesis of secondary metabolites.